2014 8th Conference of the European Study Group on Cardiovascular Oscillations (ESGCO) 2014
DOI: 10.1109/esgco.2014.6847498
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender, gestational age and behavioral states on fetal heart rate variability

Abstract: Cardiotocography (CTG) is the most frequently used electronic fetal monitoring technique, both in the antepartum and intrapartum periods. A few systems for computer analysis of CTG tracings have been developed, but there is still a large room for improvement in their capacity to diagnose fetal hypoxia/acidosis. Research on fetal heart rate (FHR) analysis has shown that several factors are not commonly considered in such systems, and these can significantly influence the computation of FHR indices: among them a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, some authors also include in the definition the value of the base excess or base deficit (127). Some authors defined as "at risk of acidemia" when pH < 7.20 (33,47,(128)(129)(130)(131)(132)(133)(134)(135)(136) or pH < 7.15 (30,121,(137)(138)(139)(140)(141)(142)(143); others define when pH < 7.1 (43,126,(144)(145)(146) or even when pH < 7.05 (38,44,48,78,(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163)(164)(165)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some authors also include in the definition the value of the base excess or base deficit (127). Some authors defined as "at risk of acidemia" when pH < 7.20 (33,47,(128)(129)(130)(131)(132)(133)(134)(135)(136) or pH < 7.15 (30,121,(137)(138)(139)(140)(141)(142)(143); others define when pH < 7.1 (43,126,(144)(145)(146) or even when pH < 7.05 (38,44,48,78,(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163)(164)(165)…”
Section: Resultsmentioning
confidence: 99%
“…In fact, an association between individual differences in prenatal heart rate and HRV and postnatal neural development has been reported ( 181 ). Besides these factors, Gonçalves et al ( 131 ) and Spyridou et al ( 182 ) noted that gender also has an effect on fHR analysis and should be considered, while Tagliaferri et al ( 183 ) found differences on both linear and non-linear indices between different ethnic groups. Gender was also shown to influence maternal heart rate (MHR) ( 52 ).…”
Section: Resultsmentioning
confidence: 99%